LEGAL PROTECTION OF EMPLOYEES WITH A SPECIFIC TIME WORKING AGREEMENT WITHIN THE FRAMEWORK OF THE RULE OF LAW STATE IN INDONESIA - Imam Budi Santoso (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2023)
Employment relationships are often carried out using a Certain Time Work Agreement (PKWT) or often called contract employees. This often happens in the practice of industrial relations in Indonesia which is sometimes made by employers by changing contracts every year with workers/labourers, even though the work carried out is work that is carried out permanently and continuously and should be done using an Indefinite Time Work Agreement (PKWTT) or often called permanent employees.  In practice, entrepreneurs often violate the provisions of PKWT which have been stipulated in the provisions of the law. Although workers/labourers have complained to the Manpower Office about the actions of employers who violate PKWT, in fact, employers are reluctant to carry out decisions or recommendations from Supervisors or Mediators to improve the status of workers/labourers from PKWT to PKWTT. Then the change of PKWT status to PKWTT in the practice of the Industrial Relations Court can be carried out by Workers / Workers if the employer violates Article 59 paragraph (1) of the Job Creation Law. This has legal consequences on the fulfillment of workers' rights in accordance with the rules applicable to PKWTT. In order to guarantee legal protection for workers, the government must make implement regulations that regulate the types and names of jobs that must be done with the PKWT category and what work must be done with the PKWTT category. As well as imposing sanctions for entrepreneurs who violate the provisions of PKWT.